Metaverse Optimization: Exploration of the Potential of Ecotourism in Geopark Merangin Jambi Based on Virtual Reality - Andriana, Septiana Dewi; Rismayanti (Brilliance: Research of Artificial Intelligence, 2024)
Merangin Jambi Geopark is a world heritage site that has been recognized by UNESCO. The attractions of the Merangin Geopark are very diverse, ranging from lakes, caves, waterfalls, hot springs, traditional forests, to ancient tree fossils that are older than the island of Sumatra (the Permian Araucarioxylon fossil is 300 million years old). Unfortunately, not many people know the beauty behind this earth park, even the Merangin Geopark is in a state of "suspended animation". The Ministry of Tourism and Creative Economy is currently working to develop the potential of the Merangin Geopark. This research is important to carry out to assist the Ministry of Tourism and Creative Economy in developing virtual reality (VR) technology to map the 3Sixty form of the potential possessed by the Merangin Geopark in an effort to introduce the Merangin Geopark. It is hoped that the aim of this research will be a breakthrough in virtual reality technology to assist the Ministry of Tourism and Creative Economy in developing Ecotourism potential in the Merangin Jambi Geopark. This research method uses a Comprehensive Life Cycle Model